Evaluation of Formosa score and diagnostic sensitivity and specificity of four Asian risk scores for predicting intravenous immunoglobulin resistance in Kawasaki disease: a bivariate meta-analysis - Chiang, Wan-Ni; Huang, Po-Yu; Kuo, Ho-Chang; Huang, Ying-Hsien; Chang, Ling-Sai (Frontiers in Cardiovascular Medicine, 2023)
Background: In 2016, Lin et al. developed a prediction score of non-responsiveness to intravenous immunoglobulin (IVIG) in patients with Kawasaki disease (KD) (Lin et al., 2016). Various studies have attempted to validate the Formosa score, but inconsistent results have given us new opportunities and challenges. The aim of this meta-analysis is to explore the role of the Formosa score as a risk score in detecting IVIG-resistant KD patients and then compare the pooled sensitivity and specificity of four Asian risk scores, Egami, Formosa, Kobayashi, and Sano risk scores. Methods: A comprehensive search of Cochrane, Embase, and PubMed was conducted through 20 December 2021. The reference lists of the included studies were manually reviewed to identify pertinent references. A random-effects bivariate model was used to estimate the summary sensitivity and specificity of the tools. Results: We found 41 relevant studies of the four Asian risk scores that were eligible to analyze for pooled accuracy. Eleven studies involving 5169 KD patients reported the diagnostic performance of the Formosa score for the risk of IVIG-resistance. The overall performance of the Formosa score was: pooled sensitivity, 0.60 (95% confidence interval [CI], 0.48 – 0.70); pooled specificity, 0.59 (95% CI, 0.50 – 0.68); and area under the hierarchical summary receiver operating characteristic curve (HSROC), 0.62. The Formosa score exhibited the highest sensitivity 0.76 (95% CI, 0.70 – 0.82) for detecting IVIG-resistant KD patients among the 21389 children included in the 41 studies. In terms of specificity estimates, Formosa had the lowest specificity 0.46 (95% CI, 0.41 – 0.51). Conclusion: Patients at high risk for IVIG resistance may receive adjunctive treatment to reduce coronary lesions and thus also cardiovascular morbidity. Among all of the included studies, we found Formosa score to have the best sensitivity (0.76) but unsatisfactory specificity (0.46) for predicting IVIG resistance in Kawasaki disease. In the future, network meta-analysis should also incorporate the accuracy of the new scores after they have undergone a certain degree of validation around the world. Trial registration: PROSPERO CRD42022341410